2023
DOI: 10.5230/jgc.2023.23.e7
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Pathology Report for Gastric Cancer: 2nd Edition

Abstract: The first edition of ‘A Standardized Pathology Report for Gastric Cancer’ was initiated by the Gastrointestinal Pathology Study Group of the Korean Society of Pathologists and published 17 years ago. Since then, significant advances have been made in the pathologic diagnosis, molecular genetics, and management of gastric cancer (GC). To reflect those changes, a committee for publishing a second edition of the report was formed within the Gastrointestinal Pathology Study Group of the Korean Society of Pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 174 publications
0
34
0
Order By: Relevance
“…Some studies included the assessment of both lymphatic and nerve invasion, which was associated with a significant prognostic impact on disease-free survival and overall survival in patients with GC with stage II or III. The study patients had a worse prognosis compared to patients who did not have lymphatic vessels and nerve invasion [23,24]. Additionally, GC patients with coexisting LVI and PNI after preoperative treatment have more advanced disease than patients without these factors or with only one of them [24].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Some studies included the assessment of both lymphatic and nerve invasion, which was associated with a significant prognostic impact on disease-free survival and overall survival in patients with GC with stage II or III. The study patients had a worse prognosis compared to patients who did not have lymphatic vessels and nerve invasion [23,24]. Additionally, GC patients with coexisting LVI and PNI after preoperative treatment have more advanced disease than patients without these factors or with only one of them [24].…”
Section: Discussionmentioning
confidence: 82%
“…The study patients had a worse prognosis compared to patients who did not have lymphatic vessels and nerve invasion [23,24]. Additionally, GC patients with coexisting LVI and PNI after preoperative treatment have more advanced disease than patients without these factors or with only one of them [24]. Lu et al showed that the invasion of lymphatic vessels is an independent prognostic factor in patients who have no lymph node metastases, i.e., N0 according to the TNM classification.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For further detailed information about the pathology for gastric cancer, please refer to the Guideline for Standardized Pathology Report for Gastric Cancer, first edition and the upcoming revised version [ 133 134 ].…”
Section: General Considerationsmentioning
confidence: 99%
“…When two or more pathological types were mixed, papillary adenocarcinoma was defined only when >50% had a papillary component, and it was classified separately as a mixed papillary-type group. 14 Pathologic staging was confirmed, including of tumor size, invasion depth, lymphovascular invasion (LVI), ulcers, and lateral and basal margin involvement.…”
Section: Methodsmentioning
confidence: 99%